A Future Lost: Artistic Appropriations of the Socialist Internationalist Legacy in Africa (KULT_online, 2017)
The publication Red Africa edited by British curator and writer Mark Nash sets out to excavate a seemingly forgotten past: the socialist friendship with Africa in the Cold War. The contributions present the results of a two-year research project and seasonal programme at Calvert 22 Foundation in London that included the exhibition Things Fall Apart, film screenings, and seminars. In the form of a collage, transcripts of conversations are assembled together with six scholarly essays and glimpses into the work of eleven artists and artist groups whose projects were on display at the exhibition. The mix of exhibition catalogue, edited volume, and glossy art magazine enters into a conversation with its readers and viewers that is equally intriguing and confusing and that leaves them wanting more.